The cat : a natural and cultural history - Brown, Sarah (Princeton University Press, 2020)
A comprehensive, richly illustrated introduction to the behavior and qualities of the catOf all the domesticated species, cats have enjoyed the most complex relationship with people-one that still leads to arguments about whether you can truly call the cat asleep by your fire "tame." The Cat is a comprehensive, richly illustrated exploration of the natural and cultural history of this much-loved pet. Chapters on Evolution & Development, Anatomy & Biology, Society & Behavior, and Cats & Humans take different angles on matters feline, offering rich information and insights about kitten development, the hierarchy of cats, how cats think, communication between cats and people, historic and extinct breeds, the challenges facing cats today and how we can help, and much, much more. The book also features a visually stunning photographic directory of more than forty popular breeds, with essential information about each. Filled with surprising facts, The Cat will enchant anyone with an interest in, or a love for, these animals.Provides a comprehensive, richly illustrated introduction to the natural and cultural history of the catOffers an in-depth discussion of behavior, including social organization, communication, courtship, and learningCovers anatomy and physiology, including mobility, predation skills, and the genetics of coat colorsFeatures clear and accessible text plus infographics, diagrams, and some 250 stunning color photographsIncludes a beautiful photographic directory to more than forty breeds